2019
DOI: 10.1111/faf.12359
|View full text |Cite
|
Sign up to set email alerts
|

Critically examining the knowledge base required to mechanistically project climate impacts: A case study of Europe's fish and shellfish

Abstract: An amalgam of empirical data from laboratory and field studies is needed to build robust, theoretical models of climate impacts that can provide science‐based advice for sustainable management of fish and shellfish resources. Using a semi‐systematic literature review, Gap Analysis and multilevel meta‐analysis, we assessed the status of empirical knowledge on the direct effects of climate change on 37 high‐value species targeted by European fisheries and aquaculture sectors operating in marine and freshwater re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…All these data may be biased because they refer to particular stocks or derive from single-factor experiments. As recognized in Catalán et al (2019), it is necessary to compare data from populations in different areas to account for phenotypic or genetic adaptation, and to analyze interactions between experimental drivers.…”
Section: Early Stage Biology Ecology and Recruitmentmentioning
confidence: 99%
“…All these data may be biased because they refer to particular stocks or derive from single-factor experiments. As recognized in Catalán et al (2019), it is necessary to compare data from populations in different areas to account for phenotypic or genetic adaptation, and to analyze interactions between experimental drivers.…”
Section: Early Stage Biology Ecology and Recruitmentmentioning
confidence: 99%
“…On land, the immediate effect of changing climate regimes on the timing of seasonal succession and processes in nature is noticed as a present-day threat to species' reproductive success (Nature Climate Change, 2018). In the marine environment, however, most attention is paid to the direct physiological effects of global ocean warming and acidification (Catalán et al, 2019). In aquatic systems, shifts in the seasonal order of natural phenomena are not as readily visible as in terrestrial systems, but have been reported from a variety of temperate oceans particularly for fish species subjected to a seasonal gradient in migration, feeding, and reproduction (Platt et al, 2003;Edwards and Richardson, 2004;Rogers and Dougherty, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Gaining a mechanistic, physiologically-based understanding of how OAW affects marine flora and fauna is essential for reliable projections of future effects of climate change [7]. Studies examining the consequences of OA on marine organisms have mainly focused on calcifying invertebrates [8, 9] with far fewer studies conducted on fish [10]. In fish, accumulating bicarbonate is a classical response aimed at regulating acid-base balance when the internal milieu acidifies.…”
Section: Introductionmentioning
confidence: 99%